Яичко: [потешная сказка] / А. Елисеев ; иллюстрации автора - Елисеев Анатолий (ЭНАС-КНИГА, 2012)
Для дошкольников. Экземпляры: (20240111) / Инвентарный номер: 36685 / Цена: 1188.00 / Сис.шифр: 84(2=411.2)6 / Авт.знак: Е 51 / ГРНТИ: 17.82.93 / ББК: 84(2=411.2)6